2012
DOI: 10.1016/j.bbamem.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning, diffusion, and ligand binding of raft lipid analogs in model and cellular plasma membranes

Abstract: Several simplified membrane models featuring coexisting liquid disordered (Ld) and ordered (Lo) lipid phases have been developed to mimic the heterogeneous organization of cellular membranes, and thus, aid our understanding of the nature and functional role of ordered lipid-protein nanodomains, termed "rafts". In spite of their greatly reduced complexity, quantitative characterization of local lipid environments using model membranes is not trivial, and the parallels that can be drawn to cellular membranes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
280
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(296 citation statements)
references
References 84 publications
13
280
3
Order By: Relevance
“…Förster resonance energy transfer (FRET) 122 is able to probe much smaller distances and has proven extremely useful for studying domain formation and phase behavior 123, 124 as well as identifying raft associating molecules 125 . FM has been also been used to study partitioning, diffusion and ligand binding of raft lipid analogs in model and cellular plasma membranes 126 . Fluorescence recovery after photobleaching (FRAP) 127 is a particularly useful approach for studying lateral diffusion in bilayers 128 and distinguishing the liquid ordered (Lo) phase in raft forming models 129,130 .…”
Section: Methods To Study Lipid Organizationmentioning
confidence: 99%
“…Förster resonance energy transfer (FRET) 122 is able to probe much smaller distances and has proven extremely useful for studying domain formation and phase behavior 123, 124 as well as identifying raft associating molecules 125 . FM has been also been used to study partitioning, diffusion and ligand binding of raft lipid analogs in model and cellular plasma membranes 126 . Fluorescence recovery after photobleaching (FRAP) 127 is a particularly useful approach for studying lateral diffusion in bilayers 128 and distinguishing the liquid ordered (Lo) phase in raft forming models 129,130 .…”
Section: Methods To Study Lipid Organizationmentioning
confidence: 99%
“…CT-and LT-binding result in the clustering of GM1 gangliosides, targeting more GM1 for retrograde transport to the ER. Both lipid sorting and toxin binding depend on lipid structure and membrane fluidity, resulting in a delicately balanced interaction network where care must be taken when performing analyses to not disturb the system under investigation [115,116]. For example, while CTB has been shown to bind preferably to ordered lipid phases [115,117], attachment of a fluorescent tag to the GM1 ganglioside partitioned CTB to the liquid disordered phase [116].…”
Section: Retrograde Transport To the Ermentioning
confidence: 98%
“…The viability of the cells was restored upon addition of cholesterol. On the other hand, depletion of cholesterol caused lipid raft disruption, and as a consequence lipid rafts were rendered nonfunctional [8]- [10]. Hence, a clear correlation seems to exist between the number of viable lipid rafts in cell membranes and the amount of available cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Observations using atomic force microscopy demonstrated that ethanol influenced the bilayer properties according to membrane lateral organization [24]. Calorimetric investigations of mixtures of ethanol and liposomes were also performed, and the results obtained showed that the addition of cholesterol in lower concentrations helped to increase the interactions, while cholesterol in higher concentrations helped reduce the interactions [8] [25].…”
Section: Introductionmentioning
confidence: 99%